Quality of life of oral and oropharyngeal cancer patients attending a tertiary care institute in Kolkata - Mallick, Debjani Basu; Dutt, Debashis; Banerjee, Bratati; Bhattacharjee, Anupam (International Journal Of Community Medicine And Public Health, 2019)
Background: Assessment of quality of life (QOL) helps to find out factors associated with disease progression and response to treatment, identify vulnerable groups. The objective of this study was to assess the QOL (based on physical, mental, social, emotional and spiritual dimensions) of oral and oropharyngeal cancer patients. Methods: A hospital based cross sectional study was conducted among 126 oral and oropharyngeal cancer patients attending radio therapy department of Calcutta Medical College. QOL was assessed by using validated Bengali version of two self-administered questionnaires: European Organization for the Research and Treatment of Cancer (EORTC)-30 and EORTC-35. Results: Among total 81 patients, most of the patients (45.67%) had stage III diseases. Median global health score (GHS) for all patients were 41.67. GHS deteriorated with advancement of the diseases (p=0.000), GHS significantly improved with increasing level of education (p=0.019). GHS was poorer among female patients (median for male was 45.66 and for female was 36.45; p=0.178) and patients with oropharyngeal cancer (median for oral cancer was 50.00, oropharyngeal cancer was 41.67, p=0.215). As per EORTC-35, pain was the major symptom for both type of cancer and was more among patients with oropharyngeal cancer. Conclusions: QOL deteriorates with advancement of the disease and is poorer among females. Co-morbidity status does not affect the QOL. Pain is a major problem of cancer patients, which is more with oropharyngeal cancer patients. Early detection of the cancer and proper pain management and counselling with special focus on females can improve the quality of life.